2015
DOI: 10.1007/s10802-015-0033-8
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Disruptive Mood Dysregulation Disorder Symptoms (Irritable-Angry Mood and Temper Outbursts) Throughout Childhood and Adolescence in a General Population Sample

Abstract: DSM-5 Disruptive Mood Dysregulation Disorder (DMDD) is a controversial new diagnosis. The DSM-5 conceptualizes DMDD as persistent and chronic, but the stability of the two DMDD symptoms (irritable-angry mood and temper outbursts) over time is not known. Mothers rated DMDD symptoms in a population-based sample of 376 children (54 % male) evaluated at 6-12 years (M 9) and again an average of 8 years later (M 16). Mean scores on irritable-angry mood plus temper outbursts at baseline and follow-up were below somet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 39 publications
(45 reference statements)
2
32
0
2
Order By: Relevance
“…Exploratory analyses, examining the subsample of participants with only ODD ( n =15), without comorbid ADHD, further support this idea, as loses temper became the central symptom of ODD (see online supplementary material). This is in line with recent longitudinal work suggesting DMDD symptoms are often components of other disorders, particularly ODD (Mayes et al, 2015). Of course, DMDD cannot be diagnosed until age 6, so it will be interesting to statistically examine symptom networks of both DMDD and ODD in older children to better understand what, if anything, differentiate the disorders.…”
Section: Discussionsupporting
confidence: 91%
“…Exploratory analyses, examining the subsample of participants with only ODD ( n =15), without comorbid ADHD, further support this idea, as loses temper became the central symptom of ODD (see online supplementary material). This is in line with recent longitudinal work suggesting DMDD symptoms are often components of other disorders, particularly ODD (Mayes et al, 2015). Of course, DMDD cannot be diagnosed until age 6, so it will be interesting to statistically examine symptom networks of both DMDD and ODD in older children to better understand what, if anything, differentiate the disorders.…”
Section: Discussionsupporting
confidence: 91%
“…The participants with ODD who met DMDD criteria did not differ significantly from their counterparts without DMDD with respect to symptom severity, comorbidity, or functional impairment 36. Other studies of clinical samples have reported similar degrees of overlap,38,48 suggesting the value of first treating the oppositional behaviors and other externalizing problems. While it is uncommon to find children with just DMDD, when it does it occur in isolation, DMDD is still associated with appreciable impairment 29…”
Section: Criticism Of Dmdd Diagnosismentioning
confidence: 74%
“…In addition, this study only examined symptom prevalence at a single time point; therefore, we cannot comment on the stability of reported symptoms. In a follow-up study of 376 children in our general population sample (Mayes et al 2015c), only 29% with DMDD symptoms at baseline had DMDD symptoms at follow-up 8 years later, and only 45% with DMDD symptoms at follow-up had DMDD symptoms at baseline (55% new cases). Axelson et al (2012) also reported low stability for DMDD symptoms in a psychiatric sample.…”
Section: Limitationsmentioning
confidence: 80%